On continuous dependence of solutions of linear differential equations on a parameter in a Banach space - Nguen, Tkhe Khoan; Fam, Ngok Boi (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove the reduction theorem for linear differential equations in a Banach space in the case where the convergence is strong. This result is used to obtain the necessary and sufficient conditions for continuous dependence of solutions on a parameter.